Three-dimensional protonic conductivity in porous organic cage solids - Ming Liu (Nature Portfolio, 2016)
Proton conduction is a fundamental process for fuel cell development, but three-dimensional proton conduction in crystalline porous solids is rare. Here, the authors report organic molecular cages in which the structure imposes three-dimensional proton conductivity competing with metal-organic frameworks.